Multidrug-Resistant Escherichia coli from Raw Cow Milk in Namwala District, Zambia: Public Health Implications - Wizaso Mwasinga; Misheck Shawa; Patrick Katemangwe; Herman Chambaro; Prudence Mpundu; Ethel M'kandawire; Chisoni Mumba; Musso Munyeme (MDPI AG, 2023)
Escherichia coli (E. coli), a major foodborne disease-causing pathogen found in raw cow milk, has even far more reaching public health ramifications as it encodes for antimicrobial resistance (AMR). This study aimed to identify multidrug-resistant (MDR) E. coli from raw cow's milk and evaluate their antimicrobial-resistant profiles. In total, 418 pooled raw cow milk samples were collected from milk collection centers and analysed using standard culture methods to isolate E. coli. Antimicrobial Susceptibility Testing (AST) was conducted using the Kirby Bauer disk diffusion method and PCR was used to identify cefotaxime (CTX) resistant genes. Overall isolation of E. coli was 51.2% (214/418) with MDR observed in 21% (45/214) of isolates across different antibiotic combinations. Resistance was observed towards ampicillin (107/214, 50%), tetracycline (86/214, 40.1%), trimethoprim/sulfamethoxazole (61/214, 28.5%), and amoxicillin/clavulanic acid (CTX) (50/214, 23.4%). Notably, 15% (32/214) resistance to CTX was observed, while 12.6% (27/214) exhibited resistance to imipenem. The blaCTX-M and blaTEM genes were detected in CTX-resistant isolates. The findings of MDR E. coli that harbour blaCTX-M and blaTEM genes in raw cow's milk indicate serious public health risks for consumers.